2008
DOI: 10.1590/s1516-89132008000600025
|View full text |Cite
|
Sign up to set email alerts
|

Plankton biomass in secondary ponds treating piggery waste

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…3 shows that even though the HRP2 operated with 30% of blocking, this pond presented the highest mean density of individuals (701,065 ind mL À1 ); on the other hand, the HRP3, with 80% of blocking, presented the lowest mean density of organisms throughout the sampling period (663,167.5 ind mL À1 ). Barthel et al (2008), studying a water hyacinth pond, observed that the hyacinth's shadow rendered the phytoplankton proliferation difficult, and the algae grazing occurrence through the zooplankton, causing lower algae density during all the nine months of monitoring.…”
Section: Composition Of the Culture Mediummentioning
confidence: 99%
See 2 more Smart Citations
“…3 shows that even though the HRP2 operated with 30% of blocking, this pond presented the highest mean density of individuals (701,065 ind mL À1 ); on the other hand, the HRP3, with 80% of blocking, presented the lowest mean density of organisms throughout the sampling period (663,167.5 ind mL À1 ). Barthel et al (2008), studying a water hyacinth pond, observed that the hyacinth's shadow rendered the phytoplankton proliferation difficult, and the algae grazing occurrence through the zooplankton, causing lower algae density during all the nine months of monitoring.…”
Section: Composition Of the Culture Mediummentioning
confidence: 99%
“…The genera Chlorella and Desmodesmus were more frequent in environments with high organic matter pollution. Barthel et al (2008) stated that Chlorella sp. was the dominant species during the entire sampling period (February-October) in their HRPs treating piggery waste, located in the south of Brazil.…”
Section: Composition Of the Phytoplankton Communitymentioning
confidence: 99%
See 1 more Smart Citation
“…The little that is known about the community composition of WSP systems is based on microscopy studies, such as those by El-Deeb Ghazy et al (2008), Barthel et al (2008), Shanthala et al (2009) and Mara (1997). Microscopy though able to give an overview of the algal groups present is unsuitable when a large number of samples require processing as it; i) relies on the expertise of well trained personnel, ii) is limited to the presence of morphological markers (which many microalgal species lack), iii) is not accurate down to species level, and iv) is very time consuming.…”
Section: Introductionmentioning
confidence: 99%
“…where SOI = specific occurrence index; Pi = frequency number of the species in the samples; P = total number of samples. The periphyton species were separated into groups according to their frequency [52]:…”
Section: Periphyton Samplingmentioning
confidence: 99%